Mental Health Status and Its Associated Factors Among Caregivers of Psychiatric Patients in Kuching, Sarawak - Ivan Vun, JS; Cheah, Whye Lian; Helmy, Hazmi (the Academy of Family Physicians of Malaysia (AFPM)., 2019)
Introduction: Caregivers have a high risk of mental health disorders. The quality of patient care is inseparable from the mental health status of caregivers. The objective of this research was to study the mental health status among caregivers of psychiatric patients and its associated factors. Method: A cross-sectional study was conducted among 198 caregivers in Kuching from January till July 2014. The respondents were recruited using systematic sampling and were required to provide information on sociodemographic and environmental factors as well as complete the Hospital Anxiety and Depression Scale (HADS) questionnaire. The data was analysed using the IBM SPSS Statistical Software Version 20.0. Results: The prevalence rates of anxiety and depression among caregivers were 32.8% and 27.8%, respectively. The caregiver’s age (OR=0.97, 95% CI = 0.953 - 0.996), the perception of caregiving as an economic burden (OR= 2.70, 95% CI= 1.256 - 5.803) and the dependence of the patient (OR= 2.27, 95% CI= 1.087 - 4.719) were associated with anxiety. A caregiver who was male (OR= 2.21, 95% CI= 1.143 - 4.262), a caretaker who held the perception that a patient was dependent on them (OR=2.53, 95% CI= 1.203 - 5.337) , and a caretaker who lacked stress-coping skills (OR=2.48, 95% CI= 1.030 - 5.973) were found to be significant factors in depression. Conclusion: A high prevalence of probable anxiety and depression among caregivers points to the need to screen caregivers. There is a vital need to train healthcare workers to be able to detect early anxiety and depression. Culturally sensitive research should be carried out for different ethnicity, and improving the support system for caregivers is necessary.